Merchandising jako narzędzie wpływu na wybory konsumenckie - Rec, Alicja (My University, 2012)
Tematem pracy jest merchandising przedstawiony jako narzędzie aktywizacji sprzedaży w sektorze handlu. Natomiast celem pracy jest przedstawienie w jaki sposób merchandising wpływa na wybory zakupowe konsumentów. Przeprowadzone zostały badania ankietowe na terenie centrum handlowego Sandecja w Nowym Sączu. Wyniki ukazały w jakim stopniu merchandising stosowany w sklepach galerii wpływa na wybory konsumentów oraz czy konsumenci są tego świadomi.

The subject of this MA thesis is merchandising (presented) as means of activation of sale in commerce. The aim of the project was examining the way in which merchandising may influence consumers' shopping choices. The author of the work conducted a questionnaire among customers of Galeria Sandecja - a shopping centre in Nowy Sącz. The research findings showed to what an extent merchandising influences consumers' shopping choices and whether or not they are aware of it.
Merchandising as a tool of influence on consumer choices
Keywords: merchandising; konsument; zachowanie; decyzje; wpływ; wybór; narzędzie; consumer; behavior; decisions; influence; choice; tool